2019
DOI: 10.1016/j.joca.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Trends in gabapentinoid prescribing in patients with osteoarthritis: a United Kingdom national cohort study in primary care

Abstract: Objective: To investigate trends in gabapentinoid prescribing in patients with osteoarthritis (OA). Methods: Patients aged 40 years and over with a new OA diagnosis recorded between 1995 and 2015 were identified in the Clinical Practice Research Datalink (CPRD) and followed to first prescription of gabapentin or pregabalin, or other censoring event. We estimated the crude and age-standardised annual incidence rates of gabapentinoid prescribing, stratified by patient age, sex, geographical region, and time sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
(35 reference statements)
2
23
0
Order By: Relevance
“…The result that a higher proportion of females in general practices was negatively associated with prescribing gabapentinoids contradicts previously published studies that female gender was associated with a higher risk of being prescribed gabapentinoids. 11,12,45 This discrepancy might be due to the limitation of applying aggregate-level data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The result that a higher proportion of females in general practices was negatively associated with prescribing gabapentinoids contradicts previously published studies that female gender was associated with a higher risk of being prescribed gabapentinoids. 11,12,45 This discrepancy might be due to the limitation of applying aggregate-level data.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies suggest that the factors influencing the prescribing of gabapentinoids and opioids were similar and gabapentinoids were increasingly co-prescribed with opioids in the UK. 2,11,45,51 According to two Canadian studies, gabapentinoid utilisation was associated with an increased risk of opioid-related death in opioid users. 52,53 Meanwhile, the potential for gabapentinoid addiction has been explored in both laboratory models and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although none of these medications are registered for OA pain in the Netherlands, it might be that general practitioners (GPs) do already prescribe these as off-label medications for OA-related pain. A recent retrospective cohort study in the UK found an almost 3-fold increase in first prescriptions of gabapentin and pregabalin in patients with OA between 2005 and 2015 [ 27 ]. Earlier studies in US insurance claims databases found 20–30% of the OA patients used an antidepressant, and around 15% used an anticonvulsant, which was higher than in patients without OA.…”
Section: Introductionmentioning
confidence: 99%